A vibrational study of phase transitions in Fe2P2O7 and Cr2P2O7 under high‐pressures. Issue 11 (28th May 2018) - Blanc, Nicolas A.; Williams, Quentin; El Bali, Brahim; Essehli, Rachid
Abstract: The vibrational properties of synthetic iron diphosphate (Fe2 P2 O7 ) and chromium diphosphate (Cr2 P2 O7 ) are studied under high‐pressure conditions between ~22 and ~30 GPa, respectively. Each compound's structural response to pressure and pressure‐induced phase transitions are characterized. The chromium‐bearing sample shows coalescence of infrared bands occurring near 6 and 17 GPa: these may be associated with increases in the local symmetry of the P2 O7 group. The iron sample undergoes a first‐order phase transition near ~9 GPa, and a possible phase transition near 5.5 GPa. At 9 GPa, the initially single, strong symmetric PO4 stretching mode splits into four modes, and the sole asymmetric PO4 stretching mode splits into two bands. These changes indicate the presence of multiple tetrahedral environments within a larger volume unit cell, and the relative frequencies of the split vibrations indicate a P2 O7 environment with a markedly narrowed P–O–P angle. The difference between the behavior of the iron and chromium compounds is probably generated by the smaller iron ion producing a discontinuous decrease in the P–O–P angle at lower pressures than in the analogous chromium compound. Our results demonstrate that the dimerized P2 O7 group remains stable under compression to over 20‐30 GPa at 300 K.